2021
DOI: 10.1038/s41598-020-79513-6
|View full text |Cite
|
Sign up to set email alerts
|

A shift towards early-age desexing of cats under veterinary care in Australia

Abstract: The global problem of unowned domestic cats, driven by their phenomenal reproductive success, carries significant economic, animal welfare and biodiversity costs. Desexing owned cats prior to puberty prevents unwanted litters that contribute to unowned cat populations. The prevalence and predictors of desexing, and the age at which surgery was carried out were investigated using anonymized electronic patient records in the VetCompass Australia database of cats presented to veterinary practices. Of 52,941 cats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Prepuberal gonadectomy has been shown to delay radial physeal closure in domestic cats, and as the age at which desexing occurred varies, this needs to be taken into consideration when assessing and applying qualitative bone measurements. [40][41][42] Due to limited evidence on the exact impact of desexing on skeletal growth, 41,42 presenting measurements as ratios rather than raw data can compensate for the variations in individual body conformation by creating a quantitative index. 43 Since knowing the lengths of metacarpals and phalanges in comparison to each other has been demonstrated as useful for surgical Mean length (millimetres), width (millimetres) and slenderness including standard deviation for tibia in male and female domestic shorthair cats.…”
Section: Discussionmentioning
confidence: 99%
“…Prepuberal gonadectomy has been shown to delay radial physeal closure in domestic cats, and as the age at which desexing occurred varies, this needs to be taken into consideration when assessing and applying qualitative bone measurements. [40][41][42] Due to limited evidence on the exact impact of desexing on skeletal growth, 41,42 presenting measurements as ratios rather than raw data can compensate for the variations in individual body conformation by creating a quantitative index. 43 Since knowing the lengths of metacarpals and phalanges in comparison to each other has been demonstrated as useful for surgical Mean length (millimetres), width (millimetres) and slenderness including standard deviation for tibia in male and female domestic shorthair cats.…”
Section: Discussionmentioning
confidence: 99%
“…Neutering of owned animals, including increased use of early-age or prepubertal neutering (before six months) and mandatory neutering prior to the sale or transfer of registered animals, will prevent unplanned breeding and possible abandonment of unwanted animals [ 104 , 105 ]. Many of the concerns regarding the effects of neutering on the health and development of cats were rebutted with empirical data in the publications arising from Belgium’s Sterycat Program [ 106 , 107 , 108 , 109 ]; however, there remains evidence that even in countries reporting a high prevalence of neutering, many cats are not neutered until later in life [ 110 , 111 , 112 ]. Groups such as Australia’s National Neutering Network ( ) or the United Kingdom’s Kitten Neutering Database (KiND, (31 August 2022)) may help to reverse this trend.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported rates of desexing related to age, with 93% of cats over the age of two being desexed [46]. However, a recent study found that from 2010 to 2017, only 60% of cats had been desexed by 6 months, and 21.5% had been desexed by 4 months of age [70], indicating that there are many cats not desexed before puberty. A high number of well-socialised kittens from owned litters are surrendered to shelters [4,37], and although many may be from stray cats with carers, a proportion are likely from owned companion cats producing kittens before they are desexed [4].…”
Section: Comparison With Laws and Regulations For Desexingmentioning
confidence: 93%
“…A 2019 review of the Western Australia Cat Act 2011 found that 37% of respondents felt the age of 6 months was appropriate, 46% were unsure, and only 16% felt it was not appropriate [69]. Desexing rates for cats are relatively high in Australia; a recent study found that 83% of companion cats are desexed [70]. Previous studies have reported rates of desexing related to age, with 93% of cats over the age of two being desexed [46].…”
Section: Comparison With Laws and Regulations For Desexingmentioning
confidence: 99%